Is there a pattern for innovative firms? A case study from a Portuguese and a Polish Region - Duarte, Nelson (2017)
The article presents the results of the study and comparison of innovation of Portuguese and Polish companies. For this research, the perspective is taken from innovation based in intangible factors, trying to measure, above all, the organizational culture of companies on innovation. The results state that Portuguese firms are less innovative than Polish ones. At the same time, in both countries manufacturing companies are more innovative than companies in the construction sector. In the case of Polish companies it was demonstrated that there was a relationship between the size and age of the innovation. The research results will be used to assess the culture of enterprises’ innovation in other countries.